PENILAIAN KINERJA BADAN USAHA MILIK DESA (BUMDes) DESA SEPAKAT KECAMATAN PLAMPANG MENGGUNAKAN KONSEP BALANCE SCORECARD - Usman, U; Wirayuda, Pangeran (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the performance of Village Owned Enterprise (BUMDes) of Sepakat Village, Plampang sub-district in 2020-2022, both of financial and non-financial performance using the Balanced Scorecard (BSC) technique. The type of this study was descriptive study. The types of data used were quantitative and qualitative data. Quantitative data was financial performance data of village owned enterprises (BUMDes) of Sepakat Village, Plampang sub-district in 2020-2022, while qualitative data was non-financial performance data of BUMDes of Sepakat Village, Plampang sub-district in 2020-2022. The data used in this study was secondary data obtained from reports contained in BUMDes of Sepakat Village. The tool used to collect data was documentation. The technique of data analysis was Balanced Scorecard (BSC) technique. The results of the study showed that the average performance value of village-owned enterprises (BUMDes) of Sepakat Village in 2020-2022 on four perspectives of the balance scorecard, namely financial perspective, customer perspective, internal business process perspective, and learning and growth perspective was 73.80 so it could be concluded that the performance of village-owned enterprises (BUMDes) of Sepakat Village in 2020-2022 was in Good category (B). It showed that the management of BUMDes of Sepakat Village had been done well so that the presence of BUMDes of Sepakat Village had been beneficial by the communities in strengthening the village economy, especially in fulfilling the needs of communities business capital.